2014
DOI: 10.1097/qai.0000000000000289
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative HIV Viremia and Non–AIDS-Defining Malignancies Among a Sample of HIV-Infected Male Veterans

Abstract: Introduction Research suggests cumulative measurement of HIV exposure is associated with mortality, AIDS, and AIDS-defining malignancies. However, the relationship between cumulative HIV and non-AIDS-defining malignancies (NADMs) remains unclear. The aim of this study was to evaluate the effect of different HIV measures on NADM hazard among HIV-infected male veterans. Methods We performed a retrospective cohort study utilizing Veterans Affairs HIV Clinical Case Registry data from 1985-2010. We analyzed the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 42 publications
3
37
0
Order By: Relevance
“…Low-to middle-income region and baseline HIV RNA were associated with risk of infection-related cancer, which reflects a higher burden of these malignancies in resource-constrained settings and suggests a stronger link between HIV RNA viremia and malignancies caused by pro-oncogenic viruses [26,27]. Older age and higher CD8 count were independent predictors of both infection-related and infection-unrelated cancer.…”
Section: Discussionmentioning
confidence: 90%
“…Low-to middle-income region and baseline HIV RNA were associated with risk of infection-related cancer, which reflects a higher burden of these malignancies in resource-constrained settings and suggests a stronger link between HIV RNA viremia and malignancies caused by pro-oncogenic viruses [26,27]. Older age and higher CD8 count were independent predictors of both infection-related and infection-unrelated cancer.…”
Section: Discussionmentioning
confidence: 90%
“…One study of 31,576 HIVinfected patients in the VA HIV Clinical Case Registry from 1985-2010 found that longer percentage of time with undetectable HIV RNA (<500 copies/mL) did not decrease HCC risk. 5 A follow-up study among 8,563 HIV/HCV-coinfected patients in this registry similarly found no association between duration of undetectable HIV RNA and HCC. 6 However, both analyses included cirrhosis as a covariate in multivariable models.…”
Section: Discussionmentioning
confidence: 76%
“…3 Despite the rising incidence of HCC among HIV-infected individuals, the determinants of this malignancy remain largely unknown in this group. 4 Three prior studies found no association between HIV suppression and risk of HCC, [5][6][7] but these studies did not evaluate the effects of longer durations or higher levels of HIV viremia, nor did they account for cirrhosis. Moreover, previous studies among predominantly HIV/HCV-coinfected patients reported that lower absolute CD4+ cell counts increased the risk of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of cART on cancer incidence is likely to be heterogeneous across cancer types. While some studies show no decreased risk of NADM as a whole for patients on cART 139,141,143 , a few large studies have identified HIV viremia as an independent risk factor for cervical cancer and anal cancer 149,151,152 , while others have found time on cART (or controlled HIV viremia) associated with decreased risk of certain non-virally associated NADM (largely lung cancer) 153 , as well as classical Hodgkin lymphoma 147 and anal cancer 152 . Differences between studies may depend in part on the definition of HIV viremia, with percent time with undetectable HIV a more sensitive measure of cART effect than single measurements of HIV viremia.…”
Section: Cancer Prevention Interventionsmentioning
confidence: 99%
“…These studies raise the hypothesis that the use of cART with consequent increase in CD4 + T-cell count and decrease in cirrhosis may be beneficial in preventing HCC. Cumulative HIV viremia has recently been associated with HCC, but this effect was no longer significant after correcting for cirrhosis 152 , suggesting cART is most beneficial before cirrhosis develops.…”
Section: Cancer Prevention Interventionsmentioning
confidence: 99%